Innovative approaches in skin therapy: bionanocomposites for skin tissue repair and regeneration - ALARÇİN, EMİNE (My University, 2024)
Bionanocomposites (BNCs) have gained significant attention in the field of biomaterials, particularly for their potential applications in skin tissue repair and regeneration. Advantages of these biomaterials in skin care and wound healing/dressings include their ability to provide a suitable environment for tissue regeneration. They can mimic the extracellular matrix, supporting cellular interactions and promoting the formation of new tissue. They can also be engineered to have controlled release properties, allowing for the localized and sustained delivery of bioactive molecules, growth factors, or antimicrobial agents to the wound site. BNCs can be used as scaffolds or matrices for bioprinting, enabling the fabrication of complex structures that closely resemble native tissue. BNC-based films, hydrogels, and dressings can serve as protective barriers, promoting an optimal wound healing environment and preventing infection. These materials can also be incorporated into advanced wound care products, such as smart dressings, which can monitor wound healing progress and provide real-time feedback to healthcare professionals. This review aims to provide a comprehensive overview of the current trends, advantages, challenges, and future directions in this rapidly evolving field. The current trends in the field are deliberated, including the incorporation of natural polymers, such as silk fibroin, hyaluronic acid, collagen, gelatin, chitosan/chitin, alginate, starch, bacterial cellulose, among others. These BNCs offer biocompatibility/biodegradability, enhanced mechanical strength, and the ability to promote cell adhesion and proliferation. However, crucial challenges such as biocompatibility optimization, mechanical property tuning, and regulatory approval need to be addressed. Furthermore, the future directions and emerging research areas are deliberated, including the development of biomimetic BNCs that mimic the native tissue microenvironment in terms of composition, structure, and bioactive cues. Furthermore, the integration of advanced fabrication techniques, such as 3D bioprinting and electrospinning, and the incorporation of nanoparticles and bioactive molecules hold promise for enhancing the therapeutic efficacy of BNCs in skin tissue repair and regeneration.
Keywords: Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; Kimya (çeşitli); Fizik Bilimleri; Genel Malzeme Bilimi; Chemistry (miscellaneous); Physical Sciences; General Materials Science